High-Performance Scientific Computing: First JARA-HPC Symposium, JHPCS 2016, Aachen, Germany, October 4-5, 2016, Revised Selected Papers - Di Napoli, Edoardo; Hermanns, Marc-André; Iliev, Hristo; Lintermann, Andreas; Peyser, Alexander (Lecture Notes in Computer Science, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the First JARA High-Performance Computing Symposium, JARA-HPC 2016, held in Aachen, Germany, in October 2016.The 21 full papers presented were carefully reviewed and selected from 26 submissions. They cover many diverse topics, such as coupling methods and strategies in Computational Fluid Dynamics (CFD), performance portability and applications in HPC, as well as provenance tracking for large-scale simulations.